1H-NMR-based metabolomics study of Rifafour in a healthy Kramnik (C3HeB/FeJ) tuberculosis mouse model - Omotayo, Oluwadara Pelumi; Bhengu, Siyethemba; Lemmer, Yolandy; Venter, Kobus; Mason, Shayne (Frontiers in Pharmacology, 2025)
Standard treatment for tuberculosis (TB) typically involves the use of four first-line medications, namely, pyrazinamide, isoniazid, rifampicin, and ethambutol. Rifafour is a tablet that consists of a combination of these four anti-TB medications. Immediate TB treatment, typically lasting up to 14 weeks in the hospital as an inpatient and up to 6 months as an outpatient, is imperative to kill the bacteria responsible for TB. However, the anti-TB medication itself is hepatotoxic and can cause several health concerns. To elucidate these metabolic consequences, this study used an untargeted 1H-NMR metabolomics approach to investigate the systemic metabolic effects of anti-TB medication administered over 14 days to healthy Kramnik (C3HeB/FeJ) mice – a mouse model commonly used in TB studies. Hippuric acid (p < 0.01), indoxyl sulfate (p < 0.05), phenylacetylglycine (p < 0.01), and tryptophan (p < 0.05) remained significantly decreased in the urine throughout the 14-day TB drug treatment period, whereas in the feces, choline (p < 0.05) and succinic acid (p < 0.01) remained consistently perturbed. Serum collected on day 14 showed significant (p < 0.05) concentrations of glucose, taurine, glycine, uracil, histamine, and allantoin, all of which were upregulated in the TB drug-treated group. This study implies that changes in systemic metabolism directly from TB treatment should be noted and considered when examining animals/patients with active TB on similar TB treatment. That is, these findings highlight the need to distinguish drug-induced metabolic abnormalities from those resulting from infections, consequently aiding the interpretation of metabolomic data in tuberculosis research and improving the development of more accurate therapeutic and diagnostic approaches. Hence, future studies can focus on the perturbed metabolites from TB and account for metabolites resulting from anti-TB medication, as shown in this study.